Imagining the flood: rationalities of governance in sinking cities - Steig, F (Frontiers Media, 2024)
The rise in global sea levels poses a substantial, sometimes existential threat to coastal cities around the world, such as Bangkok, Lagos, or Jakarta. Adaptation projects range from hard infrastructure to nature-based solutions or ‘planned retreat’, often having severe implications in terms of equity and equality. Given the threat of urban flooding and submergence, this paper asks how ‘the future’ for these cities is imagined, and how sociotechnical imaginaries of climate futures inform policymaking. Using insights from poststructuralism and Science and Technology Studies (STS), I argue that the way of ‘seeing’ and ‘knowing’ sea level rise is constitutive of the rationalities that undergird the governing of rising water around the world. I trace the discrete operations of the discursive formations and imaginaries that have evolved globally around the issue of sea level rise, with their own distinctive logics. Analyzing a variety of globally circulating policy documents and local adaptation projects, I show how the governance of sea level rise is based on a very specific ‘expert’ knowledge that allows re-designing sinking cities ‘from above’. This kind of knowledge, provided by a depoliticizing global network of consultants, designers, and development banks, privileges imaginaries of modernity and control using technology and engineering, as well as ideas on how populations in flood-prone areas are expected to govern themselves in the advent of rising sea levels. These imaginaries tend to marginalize alternative local adaptation practices, lead to unintended outcomes, and often discriminate against those who are already vulnerable to climate change impacts.